2021
DOI: 10.1021/acs.jpclett.1c02824
|View full text |Cite
|
Sign up to set email alerts
|

Graphite-like Carbon Nitride Nanotube for Electrochemiluminescence Featuring High Efficiency, High Stability, and Ultrasensitive Ion Detection Capability

Abstract: Herein, for the first time, we introduced a novel electrochemiluminescence (ECL) luminophore based on a one-dimensional g-C 3 N 4 nanotube using K 2 S 2 O 8 as the coreactant. The g-C 3 N 4 nanotube/K 2 S 2 O 8 couple displayed very satisfactory ECL performance, i.e., an ECL efficiency (Φ ECL ) of 437% (vs 100% for the Ru(bpy) 3 2+ /K 2 S 2 O 8 reference) and excellent ECL stability (the relative standard deviation (RSD) = 0.78%). By contrast, Φ ECL and RSD of the control g-C 3 N 4 nanosheet/K 2 S 2 O 8 couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…Figure 4 D shows the outstanding ECL stability of the C 3 N 4 NT-Air under continuous cyclic scans of 20 cycles, which is crucial for the sensing application. The superior stability of the C 3 N 4 nanotube can be attributed to the high specific surface area and rapid electron transfer rate of the tubular structure as our previously report [ 17 ].…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Figure 4 D shows the outstanding ECL stability of the C 3 N 4 NT-Air under continuous cyclic scans of 20 cycles, which is crucial for the sensing application. The superior stability of the C 3 N 4 nanotube can be attributed to the high specific surface area and rapid electron transfer rate of the tubular structure as our previously report [ 17 ].…”
Section: Resultssupporting
confidence: 63%
“…Lu’ group developed a nitrogen vacancy engineering strategy to improve the ECL intensity and stability, and they found that the presence of nitrogen vacancy can facilitate electron transfer and trap the excess of electrons [ 16 ]. In a previous study, our group also introduced a one-dimensional C 3 N 4 nanotube as the ECL luminophore; thanks to the high specific surface area and rapid electron transfer rate of the tubular structure, it displayed a high ECL efficiency and satisfactory stability [ 17 ]. Nevertheless, up to now, the strategies for improving the ECL properties of C 3 N 4 materials are still limited, thus it is urgent to develop new methods to increase the of ECL signal and improve the stability of C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to their excellent stability and selectivity, porous nanomaterials have a wide range of applications in the field of ECL biosensors [ 92 , 93 ]. Here, we focus on introducing the applications of ECL biosensors based on porous nanomaterials in the detection of heavy metal ions, small molecules, proteins, and nucleic acids in recent years.…”
Section: Application Of Ecl Biosensors Based On Porous Nanomaterialsmentioning
confidence: 99%
“…The Letter by Wang et al 16 reveals the anisotropic d−d transition in rutile TiO 2 and describes a systematic energy shift of electronic structure due to symmetry broken at the surface. Apart from these mechanism studies, this Virtual Special Issue also contains recent advances on synthesis, assembly, and applications of advanced materials, such as Ag 2 Se thermoelectric material, 17 2D metal−organic frameworks (MOFs), 18 Published: January 20, 2022 25 porous aromatic frameworks (PAFs), 26 a SiO x -based memristor, 27 a graphitelike carbon nitride nanotube, 28 α-C:H film, 29 light-harvesting molecular wires, 30 a bioresponsive zeolitic imidazolate framework (ZIF) system, 31 an M-PM 2−x -H 2 -based aqueous Zn battery, 32 and a MnO x @PAA@HKUST-1-DSF@BSA-based theranostic nanoagent. 33 The theoretical scientists in YIPA have always tried to explore high-throughput calculations to understand and design the functionality of advanced materials.…”
mentioning
confidence: 99%
“…reveals the anisotropic d–d transition in rutile TiO 2 and describes a systematic energy shift of electronic structure due to symmetry broken at the surface. Apart from these mechanism studies, this Virtual Special Issue also contains recent advances on synthesis, assembly, and applications of advanced materials, such as Ag 2 Se thermoelectric material, 2D metal–organic frameworks (MOFs), ZnGa 2 O 4 :Cr 3+ nanoparticles, colloidal CdSe-based nanoplatelets, Cs 4 PbI 6 –CsPbI 3 :Yb perovskite nanocomposites, Ti 3+ ion-doped CsPbCl 3 perovskite nanocrystals, carbon quantum dots, colloidal photonic crystals, a K 2 Zn 3 (SO 4 )­(HSO 4 ) 2 F 4 -based nonlinear optical crystal, porous aromatic frameworks (PAFs), a SiO x -based memristor, a graphite-like carbon nitride nanotube, α-C:H film, light-harvesting molecular wires, a bioresponsive zeolitic imidazolate framework (ZIF) system, an M-PM 2– x -H 2 -based aqueous Zn battery, and a MnO x @PAA@HKUST-1-DSF@BSA-based theranostic nanoagent …”
mentioning
confidence: 99%